Parapneumonic empyema in children - Yilmaz, E; Dogan, Y; Aydinoglu, AH; Gürgöze, MK; Aygün, D (Turkish J Pediatrics, 2002)
Forty-nine patients, aged 3 months to 13 years, were studied to determine the clinical presentation, bacteriology, treatment and outcome of empyema complicating pneumonia in children. There were 28 (57.2%) males and 21 (42.8%) females in the study, with a male/female ratio of 1.3/1. We found malnutrition in 15 (30.6%) patients. The most common symptoms at presentation were fever (93.8%) and cough (85.7%). Radiography demonstrated minimal effusions (6 patients, 12.2%), moderate effusions (23 patients, 46.9%), and massive effusions (20 patients, 40.9%). The pleural fluid was on the right side in 26 (53.1%) cases, the left side in 17 (34.6%) cases, and bilateral in 6 (12.3%) cases. Staphylococcus aureus was the most frequently isolated microorganism in pleural fluid. No organism was recovered in 33 (67.3%) patients. Most cases were treated with a combination of intravenous antibiotics and chest tube drainage. Decortication was carried out in only two patients. The hospitalization period was 28.02+/-10.18 days (11 to 57 days). There was one death due to widespread Staphylococcus aureus septicemia. All patients who were followed-up showed complete or near complete resolution of the chest radiography at six months, regardless of severity of disease or treatment modality. Children with pleural empyema can be successfully treated with appropriate antimicrobial therapy and adequate closed chest tube drainage. Further surgical intervention is rarely required.
Keywords: parapneumonic empyema; chest tube drainage